Alternative Pathway Involvement in Protoporphyria Patients Related to Sun Exposure - Granata, Francesca; Duca, Lorena; Brancaleoni, Valentina; Fustinoni, Silvia; De Luca, Giacomo; Motta, Irene; Graziadei, Giovanna; Di Pierro, Elena (Frontiers in Immunology, 2021)
The homeostasis of tissues in chronic disease is an essential function of the alternative pathway (AP) of the complement system (CS). However, if not controlled, it may also be detrimental to healthy cells with a consequent aggravation of symptoms. The protoporphyria (PP) is a rare chronic disease that causes phototoxicity at the visible light with local skin pain and general malaise. To establish, if there is a systemic involvement of the complement system during sun exposure, we designed a not invasive method with a serum collection in winter and summer from 19 PP and 13 controls to detect the levels of CS protein: Properdin, Factor H (FH) and C5. Moreover, global radiation data was collected from the regional agency of environmental protection (ARPA). The results show growing values for every protein in PP patients, compared to control, in both seasons in particular in summer compared to winter. To reinforce the evidence, we have estimated the personal exposure of patients based on global radiation data. The main factors of the AP showed increasing over the season confirming the involvement of AP about light exposure. The systemic response could justify the general malaise of patients after long light exposure and can be exploited to elucidate the new therapeutic approach.